VOTING DEVICES IN TESTING PRECONCEPTS - KAINZOVA, Veronika; Jan, RIHA; KORENA, Daniela (Trends in education, 2010)
The article introduces results of testing pre-concepts in science with usage of voting devices. Pre-concepts are an individual characteristic of each learning person. Pre-concepts are formed by various influences (school, home, native country, etc.) and the experiences. The aim of these researches resides in the pursuit of "breaking" the mistaken transcendental images and, of course, in teachers and pupils awareness of the most frequent errors in the preconcepts organization. Pre-concepts researches and the concepts changes are the basis of the constructivist conception of the scientific education.
Keywords: preconcept; misconcept; voting device.